Exploration and Research on Innovative Models for Alleviating Health Poverty in Western China's Child: a Case Study Based on the "Guguding" Medical Science Popularization and Training Program - HE Runxian, LU Wenjie, JIANG Haotian, HU Yan, LIU Qing, GAO Ye, LIU Xu (Zhongguo quanke yixue)
Mitigating child health poverty is an integral part of consolidating the achievements of poverty eradication. This paper conducts an in-depth analysis of the "Guguding" medical science popularization and training program from a public health perspective, leveraging SWOT theory and the McKinsey 7S Model. The analysis reveals that the program's value lies in overcoming challenges faced by current non-profit organizations, such as insufficient credibility, weak cultural atmosphere, limited funding sources, and lack of an effective closed-loop mechanism. By adhering to the "prevention-first" approach in health and wellness work, the program establishes a supporting system for medical hardware and software in underdeveloped regions, thereby achieving primary and secondary prevention of childhood diseases. It enhances one-on-one medical supplementation and fosters a government-oriented mechanism for medical talent retention, ultimately elevating the health standards of low-income school-age children. This endeavor further embodies the pursuit of equity and sustainable health development, serving as a proactive contribution to children, the future, and the global health cause.